2016
DOI: 10.1186/s12876-016-0420-9
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-assisted transmural cholecystoduodenostomy or cholecystogastrostomy as a bridge for per-oral cholecystoscopy therapy using double-flanged fully covered metal stent

Abstract: BackgroundLaparoscopic cholecystectomy (LC) has become the ‘gold standard’ for the treatment of symptomatic gallstones. Innovative methods are being introduced, and these procedures include transgastric or transcolonic endoscopic cholecystectomy. However, before clinical implementation, instruments still need modification, and a more convenient treatment is still needed. Moreover, some gallbladders still have good functionality and cholecystectomy may be associated with various complications. The aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 34 publications
0
32
0
1
Order By: Relevance
“…Some studies reported that EUS-GBD could be safer to perform than PTGBD in patients with anticoagulant therapy because the gastrointestinal tract is less vascular than the liver. 13,58 However, on the basis of our review, bleeding complications might occur with a certain probability, although they are rarely severe and fatal. 63…”
Section: Current Status Of Bleeding Complication In Attmentioning
confidence: 86%
“…Some studies reported that EUS-GBD could be safer to perform than PTGBD in patients with anticoagulant therapy because the gastrointestinal tract is less vascular than the liver. 13,58 However, on the basis of our review, bleeding complications might occur with a certain probability, although they are rarely severe and fatal. 63…”
Section: Current Status Of Bleeding Complication In Attmentioning
confidence: 86%
“…In their study, Barron and Topazian applied a plastic stent. Currently, however, reports on the deployment of the aforementioned lumen‐apposing metal stents have been increasing . Acute cholecystitis in cases of unresectable malignant biliary obstruction, a major complication of biliary SEMS placement, is regarded as a good indication for EUS‐GBD.…”
Section: Cutting Edge Of Interventional Eusmentioning
confidence: 99%
“…Currently, however, reports on the deployment of the aforementioned lumen-apposing metal stents have been increasing. [33][34][35][36][37][38] Acute cholecystitis in cases of unresectable malignant biliary obstruction, a major complication of biliary SEMS placement, is regarded as a good indication for EUS-GBD. The expected advantages of this technique compared to other procedures when treating acute cholecystitis are no risk of post-ERCP pancreatitis, internal drainage without the need for tube maintenance, less pain and burden on patients, and less chance of dislodgement or migration.…”
Section: Eus-guided Gallbladder Drainage and Related Interventionsmentioning
confidence: 99%
“…In 2012, we started an animal study and proved the feasibility and safety of EUS-guided transgastric cholecystolithotomy 2 . In 2015, we reported the initial attempt of EUS-assisted transduodenal cholecystolithotomy, 3 and then followed up with retrospective studies 4 , which all verified the feasibility of the technique. At that time, the procedure was accomplished by using a lumen apposing metal stent (LAMS) without a hot delivery system, which was assisted by the guidewire.…”
mentioning
confidence: 92%